From Life to Purity: Contemporary Islamic Interpretations of Death in the Thought of Jalaluddin Rahmat and Komaruddin Hidayat - Solikah, Sal Sabillah Nikmatus; Muhammad Febriansyah (Faculty of Ushuluddin and Philosophy, 2023)
Death is an inevitable reality in human life. This article examines the concept of death from the perspective of two Indonesian Muslim scholars, Jalaluddin Rakhmat and Komaruddin Hidayat, focusing on an optimistic spiritual framework. Through a qualitative method based on a literature study and comparative-critical analysis of the works Memaknai Kematian (Understanding Death) and Psikologi Kematian (The Psychology of Death), this study finds that both agree that death is a process of self-purification towards spiritual perfection. Rakhmat emphasizes death as the beginning of self-purification, while Hidayat sees it as the culmination of a purification process that takes place during life on earth. Although they share the view of death as a transition to purity, there are differences in the emphasis on the meaning of the process. This study shows that a constructive interpretation of death can inspire hope, strengthen spiritual awareness, and inspire readiness to face death with serenity. Thus, this article enriches the discourse of contemporary Islamic thought on the meaning of death as a noble existential transformation.